PEMODELAN KONTEN AUGMENTED REALITY DALAM KONSEP INTERACTIVE REALTIME - Usman Nurhasan; Eka Larasati Amalia; Budi Harijanto (IIB Darmajaya, 2020)
Augmented Reality (AR) is a new technology in real world modeling in the form of virtual objects. Aggregated reality has been developed in many mobile platforms. The information raised by augmented reality is a representation of the real world through a reference image that is a reference. Modeling that emerges from a scan of static markers in the form, color and information that appears. This obstacle is a problem that is often faced by developers from augmented reality based applications. These constraints make the existing application of augmented reality less attractive and not interactive. While one of the objectives of making augmented reality based applications is the user interaction on the application. To reduce the weaknesses found in augmented reality, one of them is to use the Live texturing concept in modeling augmented reality. This concept is a new breakthrough in the field of augmented reality. the effect of using the Live-texturing concept will give an interactive impression that is more than static augmented reality. By applying live texturing technology to augmented reality, users can provide color and texture scratches that will have a direct / real time impact on the 3D model that is displayed.